Relation between transcranial doppler findings, neuroimaging and functional state in the first days of acute cerebrovascular accidents- hemorrhagic and ischemic in patients admitted to the Ardabil city hospital during 2015-2016 - Anari, Hasan; Ardalani, Ghasem Fattahzadeh; Ghoreishi, Esmaeil; Reihany, Mortaza Delkhosh; Gholizadeh, Amir (International Journal of Research in Medical Sciences, 2020)
Background: Cerebrovascular accident (CVA) is the third leading cause of death in the United States. Considering the diagnostic and clinical value of sonography of extra cranial vessels of the brain, identifying findings obtained from patients suspected of having CVA and Transient Ischemic Attack (TIA) and their prevalence is of great importance. The aim of this study was to investigate the relation between TCD finding, neuroimaging and functional state of ischemic and hemorrhagic CVA patients. Methods: This was a cross-sectional study that has been done on 100 stroke patients admitted to Ardabil city hospital from March 2015 to March 2016. Patients underwent to CT-scan, doppler sonography, and TCD. The obtained data were analyzed by statistical methods in SPSS version 21. Results: The mean age of the patients was 66.3±11 years and 53% were women. High blood pressure, history of heart disease, smoking, and diabetes were the major risk factors in the present study. Fifty eight percent of the patients had moderate to severe disability in their functional status. Atheroma plaques, intima-media thickening, and the change of speed in the external carotid artery were most frequent in doppler sonography investigations. There was no significant correlation between the obtained results from TCD and the functional status of the patients. Conclusions: Considering the non-significant correlation between TCD results and the functional state of the patients in this study, for exactly study of this topic, study the TCD of patients on several different days and after starting treatment is essential.